Failure Modes and Resistance of Perforated Steel Rib Shear Connectors under Uplift Forces - Xiaoqing Xu; Yuqing Liu (Advances in Civil Engineering)
In recent years, there is a rapid increase in the application of perforated steel rib shear connectors in steel and concrete composite structures. The connectors must not only ensure shear transfer but also sufficient uplift resistance. The shear behavior of connectors has been extensively investigated. However, studies on uplift resistance are lacking so far. Therefore, three push-out test specimens were tested to investigate the shear and tension behavior of perforated L-shaped and plain steel rib shear connectors. The failure modes of connectors were analyzed, and analytical models for the determination of uplift resistance were derived based on test results. The results showed that the ductility of perforated steel rib shear connectors under uplift force was smaller than that under shear force, and more severe concrete damage surrounding the rib and larger bending deformation of transverse steel bar was observed. The rib flange of L-shaped perforated rib has a significant contribution to the uplift resistance. It was suggested to increase the rib height of L-shaped rib to avoid the horizontal crack at the height of the rib flange. The validity of the proposed analytical models was confirmed by comparing the failure modes and capacities of specimens.